Taxpayers 'rights and obligations under tax controls and sanctioning mechanisms on the prevention of control actions / Drepturile și obligațiile contribuabililor în cadrul controalelor fiscale și mecanismele de sancționare privind împiedicarea acțiunilor de control - ȘARGU Nicu (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
This article is a comprehensive analysis of the legal relationships between taxpayers and the State Tax Service, as well as the presentation of the consequences of deviating from the legal framework by preventing the control actions of the competent bodies. The tax legislation of the Republic of Moldova, presents in detail the rights and obligations of taxpayers, gradually describes the stages of carrying out control actions, which are published in the State Register of legal acts and the Official Gazette of Moldova, with free access for all taxpayers. Therefore, the responsibility of the taxpayers to comply with the provisions of the law is an obligation, and ignorance or knowledge of the law does not exonerate them from liability. As a consequence of non-compliance with taxpayers' obligations, the tax legislation provides for a series of sanctions. In the study, an obligation of taxpayers was identified, which does not provide for tax sanctions, and following the analysis of the legal framework, proposals for change were presented.